Control of a Variable Speed wind Energy System for Maximum Power Using Genetic Algorithm - زيدان خالد; بوشيه حسن (Latakia University Journal -Engineering Sciences Series, 2020)
This paper presents a strategy of variable speed wind turbine connected to a permanent magnet synchronous generator; the goal is to get the most possible wind turbines. We used a wind energy conversion system model consisting of a wind turbine, permanent magnet synchronous generator, rectifier, buck-boost chopper, inverter, load, and traditional controller PI to stabilize the voltage obtained from the wind turbine and synchronous generator at a variable wind speed. Then we used one of the artificial intelligence techniques represented by the genetic algorithm to get the maximum possible wind turbine. The traditional controller PI and the genetic algorithm we modeled using the Matlab R2014a program and from it we obtained the advantages of mechanical power for wind turbine and determined maximum power points at each wind speed.